P331 IMPLANT OF THE BALLOON EXPANDABLE BIOLOGICAL PROSTHESIS FOR TAVI (EDWARDS SAPIEN 3 ULTRA) PRE–ASSEMBLED ON EXPANSION BALLOON, IN "OPEN" SITUATION WITH PATIENT IN CEC. (18th May 2022) - De Remigis, F; Benvenuto, M; Tomassoni, G; Giancola, R; Tamagnini, G; De Rosa, M; Fabiani, D; Napoletano, C
Abstract: The biological valve prostheses malfunctioning often leads to severe forms of heart failure, whose treatment requires surgical or percutaneous re–intervention. We report the case of a 77–year–old man with a biological aortic prosthesis since 2009 (Elan stentless–21), hospitalized for acute cardiac decompensation related to severe aortic prosthetic insufficiency (likely infective endocarditis with periprosthesis abscess involving the perivalvular fibrous lamina) and coexistence of severe mitral insufficiency. After 25 days of therapy, in stable haemodynamic conditions, surgery was scheduled to replace the aortic prosthesis and the mitral valve, in CEC. The exposure of the aortic valve plane highlighted the rupture of the prosthetic coronary cusp in the absence of prosthetic detachment and perivalvular abscess. After removal of the degenerated cusps, the preparation and implantation of the new biological prosthesis (perimount–Magna–19) was hindered by the excessive presence of calcium–fibrosis in the suture site of the valve ring which did not allow adequate sealing, with multiple peri–prosthetics leaks; the possibility of sutureless prostheses implantation was made impossible by lack of adequate anatomical conditions. In these conditions, the possibility of implanting a biological prosthesis for TAVI, pre–mounted on the expansion balloon (Ewards–Sapien3–Ultra–23mm), in an "open" situation and in CEC, was considered. The implantation of the balloon–expandable prosthesis was performed with direct vision of the aortic annulus and coronary ostia; the insertion of the prosthesis was performed on a standard "J" guide wire positioned in the ventricle; the expansion of the prosthesis was performed in two balloon inflation steps. The intraoperative ecotransophageal echo demonstrated the correct positioning of the biological aortic prosthesis with minimal periprosthetic leak. The presence of severe residual mitral insufficiency suggested a replacement of the mitral valve with biological prosthesis. On day 4 the patient was clinically stable; the transesophageal echocardiogram showed normal functioning of the prostheses. The direct implantation of the expandable biological prosthesis in the cardiac surgery room, in "open" and CEC, after excluding active endocarditic processes and infectious complications, allowed the implantation of a larger prosthesis and to avoid significant perivalvular leaks.